ANALISIS YURIDIS PERAN DAN TANGGUNG JAWAB PPATK SEBAGAI INTELLIGENCE UNIT DALAM SISTEM PERBANKAN INDONESIA - MUAMAR ZIA NASUTION; BISMAR NASUTION; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
The development of technology and globalization in the banking sector, make the bank as the main target for money laundering activities. This is because banks as financial service providers offer many services in the traffic of financial instruments that can be used to hide/disguise the origin of the funds. Seeing so the importance of prevention and combating money laundering, then in the state must be established a Financial Intelligence agency units in Indonesia known as the Center for Financial Transaction Reports and Analysis Center (INTRAC) or term expatriate The Indonesian Financial Transaction Reports and Analysis Centre (INTRAC) which born on 17 April 2002, in conjunction with the adoption of Act no. 15 Year 2002 on Laundering. INTRAC as an entity authorized to conduct an analysis of all suspicious financial transactions are an indication of money laundering, and is one of the most important infrastructures in preventing and combating money laundering. Issues raised in the study include legal arrangements INTRAC as Financial Intelligence unit of Indonesia and the roles and responsibilities PPATK to prevent money laundering in the banking system in Indonesia. Writing this thesis research methods normative data collection library (library research) along with collecting the data and read references through regulation, the Internet and other sources, then selected appropriate data to support the writing. The results of this study are that INTRAC as a body established for the prevention and fight against money laundering gets extension with the birth of Act No. 8 of 2010 on the Prevention and combating of money laundering. One is PPATK to conduct temporary suspension of suspicious financial transactions. INTRAC role in maintaining the stability of the financial system in particular economic system of Indonesia and responsible in an effort to combat money laundering in the banking system in Indonesia, INTRAC has the authority to oversee compliance with the reporting party, in this case the banks in an effort to analyze and examine the reports and information financial transactions indicated in money laundering or other criminal received from banks. Therefore the synergy between PPATK and Banking is absolutely necessary and should further enhance cooperation in preventing money laundering is often the case in the Indonesian banking system. Keywords: INTRAC, Money Laundering, Banking.